Political Education in Increasing Student Participation as Novice Voters in Singkawang City - Sulha Sulha; Sitti Uswatun Hasanah; Andi Mursidi; I-Hasien Ting (JETL (Journal of Education, Teaching and Learning), 2023)
Secondary education students are Indonesian citizens who are categorized as first-time novice voters who are participating in political activities for the first time. Political education can increase students' awareness and knowledge in participating in politics, both in schools and in elections. This study aims to find out and analyze how political education can increase students' political participation as novice voters. This research uses a Descriptive method with research techniques for questionnaires/Google Forms, Interviews, Observations, and Documentation Studies, in high schools students throughout Singkawang City. The findings obtained by the authors in this study are that students as novice voters need to understand the importance of political education and also support activities related to political education. Based on the results of the study, it was concluded that political education for students in schools was carried out through PPKn subjects, student council activities (OSIS), Scout activities (Pramuka), and through election socialization conducted by the General Election Commission (KPU) of Singkawang City. Students who obtain such education, their political participation becomes increased. This is characterized by students being able to give opinions and arguing in the classroom, as well as having the awareness to participate and be active in organizations in the school. The political participation of students can also be seen from their readiness as novice voters, to take part in the 2024 general election.